COVERAGE AND CAUSES OF NON IMMUNIZATION IN NATIONAL IMMUNIZATION DAYS FOR POLIO; A CONSUMER AND PROVIDER PERSPECTIVE STUDY IN PESHAWAR - Naeem, Mohammad; Khan, Muhammad Zia ul Islam; Adil, Muhammad; Abbas, Syed Hussain; Khan, Ayasha; Khan, Muhammad Usman; Naz, Syeda Maria (Journal of Postgraduate Medical Institute, 2011)
Objective: Polio is a viral disease that may cause paralysis and infant death. Despite ongoing efforts, Methodology: A Cross-sectional survey was conducted in Peshawar, Pakistan, from 1st June to 9th June 2010. Confidence level of 95% and confidence interval of 4 was used to derive the sample size (for a population more than 20,000). Parents of 600 children under 5 years were asked about immunization during NIDs of January -May 2010 (5 NIDs). Questions regarding demographics, income, education, occupation, accessibility to health centres and frequency of visits from health workers was inquired. Knowledge and views on immunization were also asked. 40 health personnel involved in immunization were also interviewed and they were asked about hurdles faced in immunization. Results : 83.7% children were vaccinated in all National Immunization Days, while 94.7% had at least, taken polio vaccine once. 5.3% had not taken polio vaccine during National Immunization Days of 2010. Main reasons for not vaccinating were; Vaccinator absent/not visiting home/vaccine not available (63.36%), no awareness (17.4%), Child ill (5.8%), family problem/mother busy (3.3%) and wrong ideas/sterility (3.3%). Many health personnel (32.5%) considered lack of awareness among people and low accessibility to vaccine as the main hurdles in immunization, besides the poor salaries and incentives. Conclusion: Polio vaccination during National Immunization Days 2010 was a partial success because some pockets of poor children and afghan refugees were poorly vaccinated. In order to eradicate polio, they must be vaccinated. polio has not been eradicated from Pakistan. The purpose of this survey is to estimate the coverage of polio vaccine during National Immunization Days and to determine the factors associated with lack of immunization.